FOSMN: FACIAL ONSET SENSORY MOTOR NEURONOPATHY. A 'BENIGN' DIFFERENTIAL DIAGNOSIS TO BULBAR ONSET MOTOR NEURON DISEASE. THE FIRST COHORT FROM THE UK. Issue 11 (9th October 2013) - Ziso, Besa; Williams, Tim; Walters, Jon; Jaiser, Stephan; Wieshmann, Udo; Jacob, Anu
Abstract : Introduction: Facial onset sensory motor neuronopathy (FOSMN) is a rare, slowly progressive bulbar onset motor and sensory neuronopathy. Described only in 2006, it is still under–recognised with fewer than 20 cases reported in world literature. Although there are marked similarities to classical bulbar onset MND, FOSMN is set apart clinically by the striking facial–onset sensory deficits with subsequent development of motor deficits, slow evolution in a rostral–caudal direction and a much better prognosis. Methods: We present three cases from three different regions of the UK. Case 2 was presented at ABN 2011. A 62–year–old man presented with a three–year history of perioral paraesthesia, numbness and slurred speech, followed by upper limb weakness, fasciculations and muscle cramps. He was dysarthric, anosmic and anegusic. Sensation to pin prick and fine touch was decreased in all divisions of the trigeminal nerve bilaterally with absent corneal reflexes bilaterally. The tongue was atrophic; fasciculations were noted in the tongue and the upper limbs. Electrophysiological studies revealed widespread neurogenic changes without evidence of polyneuropathy. Extensive investigations for alternative aetiologies were unyielding. A 38–year–old woman presented with bilateral facial sensory loss. Over the following ten years she developed weakness and sensory loss in her arms and legs. Fasciculations and flaccid weakness were noted throughout her upper limbs, and there was finger drop of her fourth and fifth digits. Sensation to pinprick was reduced in her face, upper trunk and arms with some involvement distally in the legs. Proprioception and vibration sensation was normal. Horizontal saccades were slow. Electrophysiological studies revealed widespread denervation. No alternate aetiology was found on extensive testing. There was no response to repeated courses of intravenous immunoglobulin over 12 months. A 69–year–old man presented with a four–month history of numbness affecting his left cheek gradually progressing to involve his right cheek, jaw, forehead and tongue. Speech was dysarthric with reduced sensation to pinprick and soft touch in all divisions of the trigeminal nerve as well as the tongue. Over the next five years he developed wasting and fasciculations of his tongue with widespread wasting and brisk reflexes of the upper limb muscles. No alternate aetiology was detected after extensive tests. Treatment with steroids and subsequently with intravenous immunoglobulin was of no benefit. Conclusions: These three cases are similar to previously published reports and support the hypothesis that FOSMN is a sporadic, degenerative disorder distinct from typical MND. 1 TDP–43 mutations were reported by some but are not universally present. Early, accurate diagnosis is essential to allow appropriate counselling regarding the prognosis, which is much better than for bulbar onset MND with survival often exceeding ten years.